Inkremental analisis tentang desain, strategi, metodologi dan motivasi menghafal Al-Qur'an bagi tahfiz pemula - Muhammad Fatih (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
As the largest Muslim country in the world, the tradition of memorizing the Qur'an is also strong in Indonesia. Noted since before independence, many scholars of the Qur'an are born this earth. In memorizing the Qur'an people have different methods and ways. However, whatever method is used will not be separated from repeated readings to be able to say it without seeing a mushaf at all. This study aims to describe the method of memorizing the Qur'an most effectively for junior high school children. From the results of the discussion can be summarized as follows: 1. In principle all methods are good to be used as a guide memorize Al-Quran, either one of them, or used everything in accordance with the needs and as an alternative to the way memorize the monotone, so degan so will eliminate saturation in the process of memorizing Al-Quran. 2. Element tahfiz strategy should be prioritized when preparing the curriculum for teaching and learning tahfiz. Tahfiz teachers and students must focus on these strategies and apply them in tahfiz teaching and learning. This is to ensure that students achieve superior quality performance in memorizing the Qur'an.